One-pot synthesized efficient molybdenum-niobium-oxide nanocatalyst for selective C-O and C-N coupling reactions at mild conditions - Kalbande, Pavan Narayan; Singh, Nittan; Swapna, Bhattu; Umbarkar, Shubhangi; Sudarsanam, Putla (Catalysis Communications, 2023)
An efficient molybdenum-niobium-oxide nanomaterial was synthesized by a one-pot hydrothermal method for selective C-O (glycerol ketalization) and C-N coupling (benzylamine oxidation) reactions. The catalytically favourable properties, such as defective metal sites, truncated surfaces, and uniform metal dispersion in the MoO3-Nb2O5 nanorods, calcined at 500 degrees C (MoNb OPS-5), were confirmed by Raman, HR-TEM, and STEM-EDX, respectively. Because of improved Lewis/Bronsted acidic strength, the MoNb OPS-5 catalyst showed higher activity in glycerol ketalization and benzylamine oxidation at mild conditions, giving superior selectivity to solketal (97%) and dibenzylimine (99%), respectively. The MoNb OPS-5 catalyst showed high structural stability and considerable good reusability efficacy.
Keywords: C-O and C-N coupling; Glycerol and benzylamine; Mo-Nb-O nanocatalyst; nanocatalysts; One-pot hydrothermal synthesis

Efficient glycolysis of used PET bottles into a high-quality valuable monomer using a shape-engineered MnO nanocatalyst - Swapna, Bhattu; Singh, Nittan; Patowary, Suranjana; Bharali, Pankaj; Madras, Giridhar; Sudarsanam, Putla (CATALYSIS SCIENCE & TECHNOLOGY, 2024)
Keywords: Catalyst; kinetics; Nanorods; Oxidation; Oxides; POLY(ETHYLENE-TEREPHTHALATE); WASTE

Selective synthesis of renewable diesel fuel precursors via C-C condensation of biomass-derived furans using a niobium oxide nanocatalyst - Kumar, Mudavath Arun; Swapna, Bhattu; Kalbande, Pavan Narayan; Yalagandula, Lavanya; Singh, Satyapaul A.; Sudarsanam, Putla (ACS SUSTAINABLE CHEMISTRY & ENGINEERING, 2024)
Keywords: 2-Methylfuran; Catalysts; dehydration; NB2O5; RANGE ALKANES; solid acid; Valorization

Valorizing biomass waste glycerol to fuel additive at room temperature using a nanostructured WO3/Nb2O5 catalyst - Putla, Suresh Babu; Subha, P.; Swapna, Bhattu; Singh, Nittan; Sudarsanam, Putla (Catalysis Communications, 2024)
We developed a nanostructured catalyst consisting of WO3 nanoparticles and Nb2O5 nanorods for efficient glycerol acetalization to produce a fuel additive (solketal) at room temperature. Particularly, the WO3/Nb2O5 nanocatalyst calcined at 400 degrees C (WO3/Nb2O5-4) contains W5+ species and optimum acid sites, which enhanced glycerol conversion (92.3%) with 95.6% of solketal selectivity at room temperature. The structure stability of the WO3/Nb2O5-4 catalyst during the reaction is showcased by hot-filtration study and XRD/XPS characterization. However, the inadequate regeneration of the Bronsted acid sites led to a gradual decrease in the recyclable activity of the WO3/Nb2O5-4 catalyst.
Keywords: Bronsted-Lewis acid sites; Fuel additive; Room-temperature glycerol acetalization; W5+species

Additive-free, selective synthesis of N-heteroaromatics using morphology-engineered hollow CeO2 nanocatalyst - Singh, Nittan; Swapna, Bhattu; Balu, Alina Mariana; Bhatte, Kushal; Sudarsanam, Putla (ACS Sustainable Chemistry & Engineering, 2025)
We developed a highly efficient, shape-controlled CeO2 nanocatalyst for synthesizing N-heteroaromatics via an aerobic dehydrogenation approach, operating at mild reaction conditions without needing toxic acid/base additives. Different morphologies of CeO2, namely, hollow nanospheres, nanorods, and irregularly shaped nanoparticles, were synthesized, as confirmed by electron microscopy analysis. The CeO2 hollow nanosphere catalyst (CeO2-HNS) exhibited unique features, such as abundant acid-base sites, larger-sized voids, and surface oxygen vacancies. These characteristics are found to be crucial for the additive-free oxidative dehydrogenation of saturated N-heterocycles over the CeO2-HNS catalyst, resulting in 98% conversion of 1,2,3,4-tetrahydroquinoline with 100% quinoline product selectivity. The versatility of this approach was further demonstrated by the successful aerobic dehydrogenation of a broad range of saturated N-heterocycles, affording N-heteroaromatics in good to excellent yields. Furthermore, the CeO2-HNS nanocatalyst showed exceptional reusability over six cycles without requiring a regeneration step, such as high-temperature calcination treatment. The structural and morphological stability of the CeO2-HNS catalyst, along with reaction scalability and favorable green chemistry metrics, emphasized the practical viability of the CeO2-HNS catalyst for industrial applications.
Keywords: acid-base and defect sites; additive-free aerobicdehydrogenation; CeO2 hollow nanosphere catalyst; N-heteroaromatics; reusability and scalability

Liquid phase nitration of benzene to nitrobenzene using a mesoporous MoO3/Nb2O5 nanocatalyst - Kalbande, Pavan Narayan; Swapna, Bhattu; Sudarsanam, Putla; Umbarkar, Shubhangi B. (Catalysis Letters, 2025)
This work reports the synthesis of a mesoporous MoO3/Nb2O5 catalyst by a facile co-precipitation method for the liquid phase nitration of benzene to nitrobenzene, which is a vital industrial reaction. Pristine Nb2O5 and MoO3/Nb2O5 nanocatalysts were characterized using various techniques, including powder XRD, N-2 adsorption-desorption, Raman, SEM/TEM, pyridine FT-IR, and XPS. The MoO3/Nb2O5 catalyst (10 wt% MoO3 with respect to Nb2O5) showed uniform dispersion of Mo and Nb species, higher amount of oxygen vacancies, and more Br & oslash;nsted acid sites, resulting in a 90% yield of nitrobenzene. In contrast, only 35 and 58% yields were obtained in the case of commercial Nb2O5 and nanosized Nb2O5, respectively. The liquid phase nitration of benzene was carried out using commercial 65% HNO3 as a nitrating agent without sulfuric acid. The mesoporous MoO3/Nb2O5 catalyst is structurally stable, as confirmed by the characterization of the spent catalyst. However, a gradual decrease in the yield of nitrobenzene was observed, which could be due to the leaching of MoO3 species from the catalyst surface.
Keywords: Benzene nitration; Bronsted acid sites; Mesoporous MoO3/Nb2O5 Catalyst; nitrobenzene; Uniform metal dispersion